Bit-plane Encrypted Image Cryptosystem Using Chaotic, Quadratic, and Cubic Maps. Issue 6 (1st November 2016) - Kar, M.; Mandal, M. K.; Nandi, D.; Kumar, A.; Banik, S.
ABSTRACT: Recently, in chaotic cryptography several new techniques have been suggested to develop efficient and secure image encryption algorithm for communication of image over insecure/public channels. Some of these techniques are computationally less complex but fails to provide sufficient security, and some techniques are though highly secured but increases computational overhead for encryption and decryption. This paper presents an efficient bit-plane encryption algorithm using chaotic, quadratic, and cubic maps. The proposed algorithm is based on the confusion, diffusion, and pixel randomisation processes. The encryption security of this technique for different bit-plane has been tested through key space analysis, statistical analysis, entropy analysis, and sensitivity analysis for real time image encryption and transmission. The presented algorithm shows the strength of security in terms of information entropy, peak signal-to-noise ratio (PSNR), number of pixels change rate (NPCR), unified average changing intensity (UACI), and correlation coefficient with the number of encrypted bit planes. It is clear that the strength of security increases with the number of encrypted bit planes, but the presented results demand that the level of security reached to the requirements (expected theoretically according to [C. Fu, et al., Optic Express, 20, 2363–78, Jan. 2012]) after encryption of four to six bit planes with reasonable small encryption/decryption time. This features proved the novelty of the proposed work. The algorithm is tested by the random and pseudo-random sequence of test standard SP 8000-22 released by National Institute of Standard and Technology Commission (NIST).